A recurrent ZSWIM7 mutation causes male infertility resulting from decreased meiotic recombination. Issue 5 (13th March 2021) - Li, Yang; Wu, Yufan; Zhou, Jianteng; Zhang, Huan; Zhang, Yuanwei; Ma, Hui; Jiang, Xiaohua; Shi, Qinghua
Abstract: STUDY QUESTION: Are mutations in the zinc finger SWIM domain-containing protein 7 gene ( ZSWIM7 ) associated with human male infertility? SUMMARY ANSWER: The homozygous frameshift mutation (c.231_232del) in ZSWIM7 causes decreased meiotic recombination, spermatogenesis arrest, and infertility in men. WHAT IS KNOWN ALREADY: ZSWIM7 is a SWIM domain-containing Shu2/SWS1 protein family member and a subunit of the Shu complex. Zswim7 knockout mice were infertile due to impaired meiotic recombination. However, so far there is no direct evidence that mutations of ZSWIM7 cause human infertility. STUDY DESIGN, SIZE, DURATION: Screening for mutations of ZSWIM7 was performed using in-house whole-exome sequencing data from 60 men with non-obstructive azoospermia (NOA). Mice with a corresponding Zswim7 mutation were generated for functional verification. PARTICIPANTS/MATERIALS, SETTING, METHODS: Sixty Chinese patients, who were from different regions of China, were enrolled. All the patients were diagnosed with NOA owing to spermatocyte maturation arrest based on histopathological analyses and/or immunostaining of spermatocyte chromosome spreads. ZSWIM7 mutations were screened from the whole-exome sequencing data of these patients, followed by functional verification in mice. MAIN RESULTS AND THE ROLE OF CHANCE: A homozygous frameshift mutation (c.231_232del) in ZSWIM7 was found in two out of the 60 unrelated NOA patients. Both patients displayed small testicular size and spermatocyte maturation arrest in testis histology. Spermatocyte chromosome spreads of one patient revealed meiotic maturation arrest in a pachytene-like stage, with incomplete synapsis and decreased meiotic recombination. Male mice carrying a homozygous mutation similar to that of our patients were generated and also displayed reduced recombination, meiotic arrest and azoospermia, paralleling the spermatogenesis defects in our patients. LIMITATIONS, REASONS FOR CAUTION: As Zswim7 is also essential for meiosis in female mice, future studies should evaluate the ZSWIM7 mutations more in depth and in larger cohorts of infertile patients, including males and females, to validate the findings. WIDER IMPLICATIONS OF THE FINDINGS: These findings provide direct clinical and functional evidence that the recurrent ZSWIM7 mutation (c.231_232del) causes decreased meiotic recombination and leads to male infertility, illustrating the genotype-phenotype correlations of meiotic recombination defects in humans. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the National Natural Science Foundation of China (31890780, 31630050, 32061143006, 82071709, and 31871514), the Strategic Priority Research Program of the Chinese Academy of Sciences (XDB19000000), and the National Key Research and Developmental Program of China (2018YFC1003900 and 2019YFA0802600). TRIAL REGISTRATION NUMBER: Not applicable.